NUTRITIONAL IMPORTANCE DURING MENOPAUSE: A CROSS SECTIONAL STUDY IN URBAN AREA OF DISTRICT VARANASI - Verma, Pooja (Indian Journal of Community Health, 2015)
Introduction: - Menopause is a universal reproductive phenomenon. All the nutrients plays important role at the time of menopause and in prevention of diseases. Deficiency of vitamin D is one of the major contributory factors responsible for lower bone mineral density (BMD) in menopausal women. Iron deficiency anemia is common among menopausal women. The present study was conducted to assess the views on importance of nutrition & intake of various food items during menopause. Methods: - Community based cross sectional study. A total of 100 women aged 45-55 years in post-menopausal phase were selected from urban areas of district Varanasi during 2012-13. Data were collected by pretested questionnaire cum interview method. Results: - In the present study half of respondent belonged to 40-45 years age group. When they were asked about importance of nutrition during menopause 70% respondent said that they paid attention on their diet during menopause. 79% women preferred food being cooked in their kitchen. 69% women took milk in their regular diet. 95% women’s took fruits and vegetables in their diet. Only 76% have knowledge of added requirement of iron & calcium but only 59% women had iron and calcium reach foods in their regular diet. Conclusion: - In the present study about three fourth respondents knew about nutritional importance during menopause.